Sistem Fleet Management Distribusi Menggunakan Metode Saving Matrix - Lidya Siti Hafsari; Tacbir Hendro Pudjiantoro; Irma Santikarama (STMIK IKMI Cirebon, 2020)
Distribution is the activity of distributing goods from producers to consumers. Companies are obliged to optimize distribution so that they can easily compete with other companies, this can be done by optimizing the fleet. Each fleet must obtain information including the distance traveled, objectives achieved, periodic maintenance and service planning. PT Kino has 30 fleets, there is a problem where the estimated delivery time cannot be monitored because the company does not have a route plan in each shipment, this results in route optimization with the layout of goods in an unstructured fleet, from these problems the company does not have schedule reports and route planning data optimal for the achievement of the company. Another problem is that it is difficult for companies to monitor the fleet during the delivery of goods, this is because the ongoing process is still carried out in a minimalist manner which results in different reporting data between the customer and the delivery bag. The solution to overcome this problem was created a Fleet Management System using the concept of the Saving Matrix used to determine the distance and route of goods delivery from the company to consumers in order for the delivery of goods to be carried out in an effective and efficient manner. The software development method used is the waterfall. The results of this study are in the form of a system that has outputs including displaying route recommendations and monthly or yearly distribution schedule reports. After building the system, the user acceptance test was carried out with a result of 83.95% of the 41 test cases conducted by 6 actors.